2023
DOI: 10.1002/jsfa.12779
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the climate change impact of mitigation (RCP 2.6) and high emission (RCP 8.5) scenarios on maize yield and possible adaptation measures in different agroclimatic zones of Punjab, India

Abstract: BACKGROUNDA simulation study was performed for assessing climate change impact on maize under Representative Concentration Pathways (RCPs 2.6 and 8.5) for Punjab, India. The study area comprised five agroclimatic zones (AZs) including seven locations. The bias corrected temperature and rainfall data from four models (CSIRO‐Mk‐3‐6‐0, FIO‐ESM, IPSL‐CM5A‐MR and Ensemble) were used as input in CERES‐Maize model which was run with constant management practices for two Punjab maize hybrids (PMH 1 and PMH 2). The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The CERES-Wheat module of Decision Support System for Agrotechnology Transfer (DSSAT v4.7) was used for simulating the yield (Hoogenboom et al 2019). It has been widely validated and used in various environments for simulating the growth and yield of wheat (Basso, Liu, and Ritchie 2016;Qu et al 2019;Prabhjyot-Kaur et al 2023). Based upon the daily meteorological data, soil physical properties, crop management practices and cultivar-specific genotypic traits of the wheat crop, it simulates the growth and yield (Jones and Kiniry 1986;Jones et al 2003).…”
Section: Model Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The CERES-Wheat module of Decision Support System for Agrotechnology Transfer (DSSAT v4.7) was used for simulating the yield (Hoogenboom et al 2019). It has been widely validated and used in various environments for simulating the growth and yield of wheat (Basso, Liu, and Ritchie 2016;Qu et al 2019;Prabhjyot-Kaur et al 2023). Based upon the daily meteorological data, soil physical properties, crop management practices and cultivar-specific genotypic traits of the wheat crop, it simulates the growth and yield (Jones and Kiniry 1986;Jones et al 2003).…”
Section: Model Descriptionmentioning
confidence: 99%
“…org/ MarkS imGCM/ for different locations in Punjab. However, the futuristic data obtained from GCM's first need to be corrected for bias removal before further applications (Christensen et al 2008;Kaur et al 2023). So the ensemble model data on maximum, minimum temperature and rainfall was bias corrected by procedures described by Kaur et al (2020a).…”
Section: Climate Change Scenario In Punjabmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al (2019) used different climatic crop models for evaluating Chinese yield loss of maize in the future [25], while Yin and Leng (2020) found that climate variability controls 42.0% of global maize yield variations from 1980 to 2010 and historical climate trend leading to the yield loss by 1.5-3.8% during the period 1980-1990 in China [26]. Zhu et al (2021) first used hierarchical linear modeling (HLM) method for predicting maize yield in Jilin Province of China [27], Xu et al (2022) put forward that the detrimental effect of global warming on maize yield might reduce the capacity of bio-energy with carbon capture and storage (BECCS) and threaten food security in the future [28], and Kothiyal et al (2023) modeled the climate change impact of mitigation (RCP 2.6) and high emission (RCP 8.5) scenarios on maize yield and possible adaptation measures in different agroclimatic zones of Punjab, India [29].…”
Section: Introductionmentioning
confidence: 99%